Power Relations and Social Classes in Pengakuan Pariyem by Linus Suryadi AG: Reflection of Masculine Ideology - Rudi Ekasiswanto; Wisma Nugraha Christianto Richardus; Wening Udasmoro (Journal of Language and Literature, 2022)
The study aims to explore power relations and social classes as the reflections of the masculine ideology of the author in the novel Pengakuan Pariyem by Linus Suryadi AG. The theories implemented in the study are van Dijk’s power relations and social classes theory and Connell’s masculinity theory. The study is qualitative descriptive and applies the Critical Discourse Analysis (CDA) method, used to dismantle the ideology that is produced and reproduced through the language within the novel. The research data are lingual units that indicate power relations and social classes which simultaneously reflect the notion of masculinity.  The results of the study are as follows. First, Pariyem as the central character in the novel lives within a hierarchical and dualistic Javanese society. Her submission as the babu (housemaid) of a priyayi (noble) family does not only lead Pariyem to be dominated symbolically, but also legitimizes the priyayi (aristocrats) power over wong cilik (commoners).  It is reinforced by the representations of the priyayis’ world views in terms of culture, aristocracy, bureaucracy, and education orientation. It shows that priyayis are culturally dominant. Secondly, since Pariyem is a character created by a male author, her behaviors and actions reflect the ideology of masculinity. Rather than voicing women, the power relations that Pariyem experiences through the events constructed in the novel show that she embodies the masculine ideology, or masculinity.